Management of severe hyponatremia: impact of guideline adherence on clinical outcomes - Michael Reuster; Martha-Lena Stampfli; Thomas Fehr (BMC Nephrology, 2026)
Abstract Background Hyponatremia is the most common electrolyte disorder in hospitalized patients. Severe forms are associated with increased morbidity and mortality. Despite clear guideline recommendations, adherence to diagnostic and therapeutic standards is often insufficient. We analysed management of severe hyponatremia at a tertiary care hospital to explore clinical outcomes in relation to guideline adherence. Methods We performed a retrospective single-centre study at the Department of Internal Medicine, Cantonal Hospital Graubünden, Switzerland. Between September 2016 and December 2019, 199 adult patients with severe hyponatremia (serum sodium < 125 mmol/L) were included. Diagnostic work-up was evaluated based on completion of the minimal diagnostic standard and documentation quality in the electronic health record. Therapeutic management was assessed with emphasis on cumulative fluid intake within the first 48 h. Outcomes included overcorrection, length of stay, rehospitalization, and mortality. Results The minimal diagnostic standard was complete in 61% of patients. In separate univariable models, mDS completion was associated with lower odds of mortality at all assessed time points, including in-hospital mortality (OR 0.25, p = 0.008), mortality within 6 months (OR 0.24, p = 0.001), and mortality within 12 months (OR 0.28, p = 0.002). Documentation quality was poor, with complete diagnostic information on tonicity and volume status recorded in only 15% of cases. Relative to complete documentation, absence of hyponatremia from the diagnosis list was associated with higher odds of in-hospital death (OR 5.33, p = 0.047), death within 6 months (OR 9.88, p = 0.005), and death within 12 months (OR 6.35, p = 0.010). Half of patients received more than 2000 mL of fluids within 48 h. Overcorrection was detected in 20% of evaluable patients and was associated with higher fluid volumes (2001–3000 mL: OR 6.06, p = 0.029; >3000 mL: OR 10.32, p = 0.003). The 24-hour increase in serum sodium differed according to mDS completion and documentation quality. No cases of osmotic demyelination syndrome were documented. Conclusion In patients with severe hyponatremia, completion of the guideline-recommended diagnostic work-up and thorough documentation identified patients with lower odds of mortality in univariable analyses, whereas higher fluid volumes were associated with documented overcorrection. Structured diagnostic assessment, documentation, careful fluid administration, and sodium monitoring may represent quality-of-care targets in this high-risk population.